Mechanistic Models Predict Efficacy of CCR5‐Deficient Stem Cell Transplants in HIV Patient Populations - I Hosseini; F Mac Gabhann (CPT: Pharmacometrics & Systems Pharmacology, 2016)
Combination antiretroviral therapy (cART) effectively suppresses viral load in HIV‐infected individuals, but it is not a cure. Bone marrow transplants using HIV‐resistant stem cells have renewed hope that cure is achievable but key questions remain e.g., what percentage of stem cells must be HIV‐resistant to achieve cure?. As few patients have undergone transplants, we built a mechanistic model of HIV/AIDS to approach this problem. The model includes major players of infection, reproduces the complete course of the disease, and simulates crucial components of clinical treatments, such as cART, irradiation, host recovery, gene augmentation, and donor chimerism. Using clinical data from 172 cART‐naïve HIV‐infected individuals, we created virtual populations to predict performance of CCR5‐deficient stem‐cell therapies and explore interpatient variability. We validated our model against a published clinical study of CCR5‐modified T‐cell therapy. Our model predicted that donor chimerism must exceed 75% to achieve 90% probability of cure across patient populations.